Distributed Leadership and New Generation Employees’ Proactive Behavior: Roles of Idiosyncratic Deals and Meaningfulness of Work - Xu, Shuhui; Zhang, Haomin; Dai, Yi; Ma, Jun; Lyu, Ledi (Frontiers in Psychology, 2021)
New generation employees have become the main force of the organization, and their proactive behavior directly affects the organization’s future development. How to effectively stimulate the proactive behavior of new generation employees has become a hot topic in the field of organizational management. Based on the integrated perspective of social exchange and self-enhancement, we constructed a multistep mediation model to explore the influence mechanism of distributed leadership on the proactive behavior of new generation employees. We designed a three-stage research method of supervisor-employee pairing to collect data from 26 supervisors and 304 new generation employees in a new energy vehicle company in East China. Results indicated that (a) distributed leadership is positively related to proactive behavior of new generation employees; (b) idiosyncratic deals and meaningfulness of work mediated the linkage between distributed leadership and new generation employees’ proactive behavior; (c) idiosyncratic deals and meaningfulness of work play a multistep mediation role between distributed leadership and new generation employees’ proactive behavior. These findings have theoretical implications for the proactive behavior literature and managerial implications for practitioners.